CONDITIONS AND FACTORS OF DEVELOPING RUSSIAN SELF-REGULATING INSTITUTION - A. N. Ryahovskaya (Real Economics Publishing House, 2015)
Having highly developed civil society institutions and efficient dialog with state authorities of all the power levels is a prerequisite, the base for successful implementation of self-regulation, but not the opposite – forming SRO for civilian initiative growth, like it happens in Russia. The article shows flaws in professional societies’ work in managing housing facilities, discovers ways to improve functioning mechanism and regulatory and legal framework of self-regulation institution.